Analisa Kinerja Inkubator Bisnis Menggunakan Metode Performance Prism dan Analytical Hierarchi Process - Wowiling, Novie CH; Hardjomidjojo, Hartrisari; Muhandri, Tjahja (Institut Pertanian Bogor, 2025)
Research on the performance of IPB business incubators is based on observations from various stakeholders to sharpen strategies and improve performance that has an impact on improving business incubator services in encouraging the birth of start-up business actors, especially in the IPB environment and generally in the community. The stakeholders in question are leaders, employees, tenants, regulators and the community. The research objectives are to design KPIs, determine KPI priorities, and provide suggestions for improvements to Key Performance Indicators (KPI). Therefore, it is necessary to carry out a performance measurement method based on Performance Prism with 5 perspectives, namely satisfaction, contribution, process, strategy and capability. The design and measurement of performance in this study was carried out in stages, namely an analytical hierarchy process to determine the priority value scale of each KPI process, strategy and capability based on AHP and assessment of satisfaction and contribution with the Likert scale. The results of measuring performance between stakeholders including KPI Strategy involving leaders, employees and tenants are very important.